ANALISIS PROGRAM LITERASI SEKOLAH TERHADAP MOTIVASI DAN MINAT PESERTA DIDIK DI SMK KOTA MAKASSAR - Wirda Angraiani; Riana T. Mangesa; Abdul Muis Mapalotteng (UNM Journal of Technology and Vocational, 2022)
This study aims to determine: (1) The influence of the school literacy program on the motivation of students in the Makassar City State Vocational School, (2) The influence of the school literacy program on the interest of students in the Makassar City State Vocational School (3) The joint influence between school literacy, motivation and interest in learning at SMK Negeri Makassar City. The population in this study were students at the Makassar City State Vocational School. then a sample of 101 students was taken. Collecting data using a questionnaire, observation and documentation. Test requirements analysis by testing data normality, linearity and homogeneity. Analysis of the data used in the form of regression analysis to answer the formulation of this research problem. The results of this study indicate the following: (1) there is a significant effect. This shows that learning motivation contributes 50%. (2) there is a significant effect. This shows that interest in learning contributes 81%. (3) there is a joint influence of school literacy, motivation and interest in learning at SMK Negeri Makassar City by contributing 81%.